Influence of short-term hydrographic variations during the north-east monsoon on picophytoplankton community structure in the eastern Arabian Sea. (15th August 2017) - Rajaneesh, K.M.; Mitbavkar, Smita; Anil, A.C.
Abstract: The eastern Arabian Sea over the continental margin is a dynamic region subjected to short-term variability in hydrography as a result of various physical forcing such as coastal advection and vertical mixing. In order to assess the influence of hydrography on the picophytoplankton community, a temporal high resolution (every 3 h for nine days) study was carried out at a fixed location (15° 18′ 46″N, 72° 41′ 53″E) in the eastern Arabian Sea during the early north-east monsoon (November 2011). The picophytoplankton community comprised of Synechococcus, Prochlorococcus, and picoeukaryotes. Based on the temperature and salinity distribution, the study period was divided into phase I representing a stratified water column and phase II representing a vertically mixed water column. Phase I had higher picophytoplankton abundance with the initial dominance of Prochlorococcus which was later taken over by picoeukaryotes. Towards the end of phase I, with the initiation of vertical mixing, picoeukaryotes were the first to respond to the nutrient influx. As the vertical mixing intensified during phase II, the picophytoplankton abundance declined. Picophytoplankton carbon biomass and their contribution to total phytoplankton biomass was relatively higher during phase I with picoeukaryotes as the major contributors. These transient variations in picophytoplankton abundance highlights the importance of high frequency observations at the single cell level for better understanding the population dynamics in such environments. Highlights: Assessed eastern Arabian Sea picophytoplankton community via high resolution sampling. Picophytoplankton better adapted to stratified than vertically mixed waters. Picoeukaryotes dominated the transition phase from stratified to vertical mixing. Picoeukaryote dominance during transition phase is ascribed to internal tides. Transient variations highlight importance of high frequency observations.